ASSESSING L2 WRITING IN THE ABSENCE OF SCORING PROCEDURES: CONSTRUCTION OF RATING SCALES IN A CYPRIOT-GREEK EFL IN CLASS CONTEXT - Elena Kkese (Universitas Sembilanbelas November Kolaka, 2018)
Two central issues in the assessment of direct writing tests, especially for L2 contexts, refer to the development of these tasks and the scoring procedures. These allow making inferences about the specific test takers’ writing ability and provide useful diagnostic information about what aspects of writing are mostly important for raters. This study was concerned with constructing specific rating scales based on written samples by Cypriot-Greek students in an EFL classroom context in an effort to examine and determine what aspects of writing are more important in L2 writing and how are these divided up. The examination of these written samples was conducted using two different approaches in an effort to come up with valid and reliable ways to evaluate L2 written samples. The developed rating scales addressed overall writing ability and spelling accuracy. The findings suggest that more emphasis on L2 writing may be given to accuracy rather than communicative effectiveness drawing attention to the need of involving tasks that provide the opportunity to students to reflect on content or topical knowledge.